Quantification and localization of hesperidin and rutin in Citrus sinensis grafted on C. limonia after Xylella fastidiosa infection by HPLC-UV and MALDI imaging mass spectrometry. (July 2015) - Soares, Márcio Santos; da Silva, Danielle Fernandes; Forim, Moacir Rossi; da Silva, Maria Fátima das Graças Fernandes; Fernandes, João Batista; Vieira, Paulo Cezar; Silva, Denise Brentan; Lopes, Norberto Peporine; de Carvalho, Sérgio Alves; de Souza, Alessandra Alves; Machado, Marcos Antônio
Abstract : Graphical abstract: HPLC-UV and MALDI imaging on citrus with citrus variegated chlorosis (CVC) showed higher concentrations of hesperidin in infected plants than in healthy ones. Highlights: MALDI imaging mass spectrometry was applied to study the tissue distribution of hesperidin. HPLC-UV analyses of citrus with citrus variegated chlorosis (CVC) showed hesperidin was at higher concentration in leaves. HPLC-UV analyses can screen many samples for CVC per hour using about 1 mg of leaves. Hesperidin has a role in plant–pathogen interaction, probably as a phytoanticipin. Increase in hesperidin content can be related to induced defense mechanisms. Abstract: A high performance liquid chromatography-ultraviolet (HPLC-UV) method was developed for quantifying hesperidin and rutin levels in leaves and stems of Citrus limonia, with a good linearity over a range of 1.0–80.0 and 1.0–50.0 μg mL −1 respectively, with r 2  > 0.999 for all curves. The limits of detection (LOD) for both flavonoids were 0.6 and 0.5 μg mL −1, respectively, with quantification (LOQ) being 2.0 and 1.0 μg mL −1, respectively. The quantification method was applied to Citrus sinensis grafted onto C. limonia with and without CVC (citrus variegated chlorosis) symptoms after Xylella fastidiosa infection. The total content of rutin was low and practically constant in all analyses in comparison with hesperidin, which showed a significant increase in its amount in symptomatic leaves. Scanning electron microscopy studies on leaves with CVC symptoms showed vessel occlusion by biofilm, and a crystallized material was noted. Considering the difficulty in isolating these crystals for analysis, tissue sections were analyzed by matrix-assisted laser desorption / ionization mass spectrometry imaging (MALDI MSI) to confirm the presence of hesperidin at the site of infection. The images constructed from MS/MS data with a specific diagnostic fragment ion ( m / z 483) also showed higher ion intensities for it in infected plants than in healthy ones, mainly in the vessel regions. These data suggest that hesperidin plays a role in the plant-pathogen interaction, probably as a phytoanticipin. This method was also applied to C. sinensis and C. limonia seedlings, and comparison with the graft results showed that the rootstock had an increased hesperidin content ∼3.6 fold greater in the graft stem than in the stem of C. sinensis seedlings. Increase in hesperidin content by rootstock can be related to induced internal defense mechanisms.